A Mixed Methods Study Exploring Older Womens' Attitudes Toward Osteoporosis Medications: Adapting a Health Communication Framework - Lindsay N. Fuzzell; Liana Fraenkel; Susan L. Stark; Sarabjeet S. Seehra; Christine Nelson; Audrey Keleman; Mary C. Politi (Mary Ann Liebert, 2020)
Background: Bisphosphonates (BPs) can reduce fracture risk for adults with osteoporosis (OP), but they have rare risks, complicating decision making. Guided by an established health decision and communication framework, we explored older women's feelings and positions toward taking BPs. Materials and Methods: Using a mixed-methods design, we interviewed women >65 years of age who had never taken BPs. After learning about BPs, participants responded to items about their feelings toward medication benefits/risks. They then identified their overall position toward taking BPs (corresponding to Unquestioning Acceptors, Cautious Acceptors, Hesitants, Probable Refusers, and Definite Refusers). We analyzed data using qualitative content analysis and summarized quantitative data with descriptive statistics. Results: Thirty women participated. Acceptors (N?=?17, 56.6%) worried about OP-related fractures. Hesitant participants (N?=?12, 40%) worried about BP risks, yet expressed openness toward medications if given opportunities to gather information and talk to clinicians. One Refuser expressed distrust in clinicians and pharmaceuticals. Conclusions: Understanding women's positions toward BPs might improve decision-making processes for OP treatment. Clinicians could tailor communication based on patients' identified BP position. Acceptors might be comfortable with succinct conversations describing medications. Hesitant patients might need more information from resources such as decision aids. Building trust with patients questioning BPs can support future conversations.